Use of natural anterior maxillary teeth in immediate removable partial denture: An old technique revisited - Varun Baslas; Simranjeet Kaur; Rohit Yadav; Himanshi Aggarwal; Mohammad Ehtisham (Wolters Kluwer Medknow Publications, 2016)
Maxillary anterior teeth play an important role in esthetics, speech, smile, and self-esteem of an individual. Although a clinician can restore missing teeth with artificial teeth, the importance of natural teeth in patient's overall personality cannot be ignored. The present article elucidates a technique for fabrication of immediate removable partial denture prosthesis using natural teeth to enhance esthetics and confidence of the patient.